Features of Gaia DR3 spectroscopic binaries I. Tidal circularization of main-sequence stars. Issue 1 (5th April 2023) - Bashi, Dolev; Mazeh, Tsevi; Faigler, Simchon
ABSTRACT: Previous studies pointed out that many observed samples of short-period binaries display a cut-off period, P cut, such that almost all binaries with periods shorter than P cut have circular orbits. This feature is probably due to long-term circularization processes induced by tidal interaction between the two stars of each binary. It seemed as if coeval main-sequence (MS) samples of open clusters display P cut that depends on the sample age. Using the unprecedentedly large sample of MS spectroscopic orbits recently released by Gaia, we have found that the P cut does not depend on the stellar age but, instead, varies with stellar temperature, decreasing linearly from 6.5 d at T eff ∼ 5700 K to ∼2.5 d at 6800 K. P cut was derived by a new algorithm that relied on clear upper envelopes displayed in the period-eccentricity diagrams. Our P cut determines both the border between the circular and eccentric binaries and the location of the upper envelope. The results are inconsistent with the theory, which assumes circularization occurs during the stellar MS phase, a theory that was adopted by many studies. The circularization has probably taken place at the pre-main-sequence phase, as suggested already in 1989 by Zahn and Bouchet, and later by Khaluillin and Khaluillina in 2011. Our results suggest that the weak dependence of P cut on the cluster age is not significant, and/or might be due to the different temperatures of the samples. If indeed true, this has far-reaching implications for the theory of binary and exoplanet circularization, synchronization, and alignment.